The relationship between male factor infertility and Chlamydia infection, still an undecided issue - Ishrat, Shakeela; Hossain, Marufa; Jahan, Shirin; Nazneen, Sohely; Chowdhury, Fahmida; Karim, Satu Farhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Seropositivity of Chlamydia trachomatis in men is suggestive of chronic and recurrent infection with this sexually transmitted organism. Most males with urogenital Chlamydia infection have serum immunoglobulin G (IgG) antibodies to C. trachomatis that persist for years. Serologic studies linking C. trachomatis to male infertility and sperm quality lead to highly variable results. The objective of the study was to examine the effect of Chlamydia infection, as determined by Chlamydia seropositivity on semen quality. Methods: One hundred men having semen analysis as part of infertility work up had anti-Chlamydia antibody test. They were grouped into those who are seropositive for Chlamydia antibody IgG and those who were not. The sperm parameters and prevalence of different semen abnormalities were compared between the two groups, Chlamydia positive and Chlamydia negative. Results: There are no significant difference in semen parameters and prevalence of different semen abnormalities between the two groups. The sonographical finding of epididymal cyst is 45.8% in Chlamydia positive compared to 12.2% in Chlamydia negative; the difference is significant. Conclusions: Seropositivity of Chlamydia infection in infertile male is not predictive of semen abnormalities. Serological screening of the male partner for Chlamydia trachomatis provides no more benefit than identifying the female partner at risk of tubal factor infertility and males at risk of epididymal obstruction.